Social and labour dimensions of globalization and integration process : experience of CARICOM - Mark, Wade (ILO LimaPE, 2002)
Refers to the different aspects that are related to the social scope of globalization and the integration process that is under way, particularly in CARICOM. Analyzes labour institutions associated to the integration process. Shows the different aspects tackled by all countries and in particular in those economies where labour reforms were introduced to adapt productive processes to the new realities of an ever changing world. Focuses on the different concerns related to the modernization of labour management countries. Includes an updated answer to new labour requirements and challenges. Looks at the issue of conflict and the steps for treating it.